2018
DOI: 10.1016/j.jclepro.2017.11.176
|View full text |Cite
|
Sign up to set email alerts
|

Integrating the environmental and social sustainability pillars into the lean and agile supply chain management paradigms: A literature review and future research directions

Abstract: Established supply chain management paradigms such as leanness, agility, and sustainability have received increased attention in the literature, but mainly as separate topics. However, while the importance of sustainability as a competitive priority has grown significantly in recent years, companies still try to reconcile the pressures of enhancing their supply chain efficiency and effectiveness. Thus, understanding what is the best way for companies to design and implement a system of practices that meets, on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
121
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(144 citation statements)
references
References 79 publications
2
121
0
6
Order By: Relevance
“…This circumstance, together with the development of social awareness regarding human rights and the protection of the environment, has led to a growing interest in sustainability [3]. This is manifested in the proliferation of academic studies on sustainability in different fields of knowledge, such as economy (e.g., [4,5]), management (e.g., [6,7]), sociology (e.g., [8,9]), etc. International organizations such as the United Nations (UN) show also an increasing concern for sustainability.…”
Section: Introductionmentioning
confidence: 99%
“…This circumstance, together with the development of social awareness regarding human rights and the protection of the environment, has led to a growing interest in sustainability [3]. This is manifested in the proliferation of academic studies on sustainability in different fields of knowledge, such as economy (e.g., [4,5]), management (e.g., [6,7]), sociology (e.g., [8,9]), etc. International organizations such as the United Nations (UN) show also an increasing concern for sustainability.…”
Section: Introductionmentioning
confidence: 99%
“…TPM is another lean tool that was linked with solutions to some economic, environmental, and social sustainability issues [8,101,225,226]. TPM was often referred as one of the most effective waste elimination tools [142,151,249]. In a past study, TPM was shown to be among ten lean tools that simultaneously help with productivity and environmental efficiency [4].…”
Section: Tools and Methods Constructmentioning
confidence: 99%
“…The authors supported their claim with outcomes of a case study for aerospace industry. In the most recently published review article, Ciccullo et al, (2018) have evaluated lean-sustainability and agile-sustainability integration under six categories to identify the characteristics of integration within the scope of supply chain performance [142]. They found that the most common characteristic of lean or agile integration with sustainability was as a supporting paradigm followed by their integration characteristic as a precursor to sustainability.…”
Section: Past Literature Reviewsmentioning
confidence: 99%
“…The research explores the challenges facing organizations in aligning sustainable procurement requirements and the attendant shifts in supply chain management practices (green practices). [46,50,51]…”
Section: Thematic Interest Aspects Referencesmentioning
confidence: 99%